Fire Resistance of Structural Concrete Retrofitted with Carbon Fiber–Reinforced Polymer Composites. Issue 1 (January 2015) - Reddy, D. V.; Sobhan, Khaled; Young, Jody D.
This paper presents an experimental investigation for evaluating the effects of fire exposure on properties of structural elements retrofitted by carbon fiber–reinforced polymers (CFRPs). Mechanical properties of CFRP-strengthened reinforced concrete (RC) members, protected with secondary insulation, were investigated, before and after (residual) direct fire exposure. Direct fire contact resulted in a reduction in capacity of 9% to 20% for CFRP-strengthened RC beams and 15% to 34% for CFRP-strengthened RC columns. Furthermore, a similitude analysis was developed for a heat transfer relationship between full-scale and small-scale specimens, allowing a one-fourth exposure time reduction for the latter. Results from the experimental investigations demonstrated the benefits of employing secondary fire protection to CFRP-strengthened structures, despite the glass transition temperature being exceeded in the early stages of the elevated-temperature exposure. Therefore, it is suggested that fire protection is necessary for a CFRP-strengthened structure to retain integrity throughout the duration of the fire exposure and on return to ambient temperature. The conclusions of this investigation will lead to recommendations and guidelines to designers and practicing engineers for using CFRP materials in retrofitting RC structures with adequate fire resistance by contributing to the missing information for fire protection requirements not available in codes of practice.